Atlas of health in Europe : 2nd edition 2008 (WHO Regional Office for Europe, 2008)
This updated statistical atlas presents key health figures for the WHO European Region. They cover basic data on populations, births, deaths, life expectancy and diseases, lifestyle and environmental indicators, such as drinking, smoking and traffic accidents, and types and levels of health care.Each indicator is presented as a map to show overall regional variations, a bar chart to indicate country rankings and a time chart to show trends over time in three main country groupings.Using the WHO Regional Office for Europe’s unique Health for All database, combined with the best alternative sources of data around the Region, this atlas offers the most comprehensive overview of health in Europe. In a handy size, this atlas is designed to be an easily accessible resource at all times, in the office or on the road.
Keywords: mortalita; Health Status Indicators; veřejné zdravotnictví; Vital Statistics; statistika přirozeného pohybu; morbidita; Morbidity; demografie; Evropa; Mortality; Health Surveys; Europe; ukazatele zdravotního stavu; zdravotnické přehledy